Hubungan Tahap Kualiti dengan Kepuasan Pelanggan Menggunakan Perkhidmatan Pelabuhan di Malaysia: Kajian Kes di Johor Port Sdn. Bhd. - Nur Aisyah Nellydia Ramli,; Fazian Hashim, (Research in Management of Technology and Business, 2024)
Port services play an important role in the various types of services provided by ports to facilitate the transportation of goods from one location to another. However, inefficient management and not being able to provide quality services cause less interest and customer dissatisfaction with the use of port services. Therefore, this study aims to identify the level of service quality and satisfaction of customers who use port services at Johor Port Sdn. Bhd. The SERVQUAL model will be used in this study to evaluate the level of service quality based on 5 dimensions such as tangibility, assurance, reliability, responsiveness, and empathy. This study focuses on users who use port services at Johor Port. The study sample consisted of 234 users of Johor Port port services as respondents in this study. Data will be analyzed using descriptive and correlational methods to conduct this study. Quantitative methods are used, where questionnaires are to be distributed to obtain data from customers using port services at Johor Port Sdn. Bhd. Statistical Package Software for the Social Sciences (SPSS) is used to analyse the data collected. In conclusion, the significant findings of this study can contribute to provide useful information to the Johor Port Sdn. Bhd. in improving service quality and meeting customer needs.